Challenges to Ebola preparedness during an ongoing outbreak: An analysis of borderland livelihoods and trust in Uganda - Schmidt-Sane, Megan M; Nielsen, Jannie O; Chikombero, Mandi; Lubowa, Douglas; Lwanga, Miriam; Gamusi, Jonathan; Kabanda, Richard; Kaawa-Mafigiri, David (Public Library of Science, 2020)
Ebola Virus Disease in the Democratic Republic of Congo (DRC) was declared a public health emergency of international concern on July 17, 2019. The first case to cross the border into Uganda in June 2019 demonstrates the importance of better understanding border dynamics in a context of Ebola. This paper adopts a political economy approach to contextualize epidemic response programs conducted in moderate- and high-risk border districts in Uganda, through a qualitative study with 287 participants. To that end, our aim was to describe the historical underpinnings of the borderlands context; the role of livelihood strategies in constraining risk avoidance decisions; and the dynamics of trust in authority figures, including health workers. This paper reports that border communities are highly connected, for a variety of social and economic reasons. These daily realities are in direct opposition to guidance to limit travel during an active Ebola epidemic. We argue that an ability to limit movement is constrained by the economic need to seek livelihood strategies wherever that may be. Moreover, border regions are populated by communities with long-standing distrust in authority figures, particularly in fishing areas. This distrust spills over with consequences for Ebola prevention and control activities. This research indexes the importance of tailoring Ebola programming and policies to consider the political and economic dynamics of borderlands.